Changes in kinematics and aerodynamics over a range of speeds in Tadarida brasiliensis, the Brazilian free-tailed bat - Hubel, Tatjana Y.; Hristov, Nickolay I.; Swartz, Sharon M.; Breuer, Kenneth S. (Zenodo, 2012)
(Uploaded by Plazi for the Bat Literature Project) To date, wake measurements using particle image velocimetry (PIV) of bats in flight have studied only three bat species, all fruit and nectar feeders. In this study, we present the first wake structure analysis for an insectivorous bat. Tadarida brasiliensis, the Brazilian free-tailed bat, is an aerial hunter that annually migrates long distances and also differs strikingly from the previously investigated species morphologically. We compare the aerodynamics of T. brasiliensis with those of other, frugivorous bats and with common swifts, Apus apus, a bird with wing morphology, kinematics and flight ecology similar to that of these bats. The comparison reveals that, for the range of speeds evaluated, the cyclical pattern of aerodynamic forces associated with a wingbeat shows more similarities between T. brasiliensis and A. apus than between T. brasiliensis and other frugivorous bats.